Partial Rotator Cuff Repair With Superior Capsular Reconstruction Using the Biceps Tendon Is as Effective as Superior Capsular Reconstruction Using a Tensor Fasciae Latae Autograft in the Treatment of Irreparable Massive Rotator Cuff Tears. Issue 6 (3rd June 2020) - Kocaoglu, Baris; Firatli, Goktug; Ulku, Tekin Kerem
Background: Several treatment options are available for stable massive rotator cuff tears, including partial repair with or without tissue augmentation, tendon transfer, superior capsular reconstruction (SCR), and reverse shoulder arthroplasty. Purpose/Hypothesis: The purpose of this study was to compare the outcomes and effectiveness of partial rotator cuff repair with SCR using the long head of the biceps tendon (PRCR-SCRB) and SCR with a tensor fasciae latae autograft (SCRTF) for the treatment of rotator cuff tears with severe fatty degeneration. The hypothesis of this study was that SCRTF would be superior to PRCR-SCRB in functional and anatomic outcomes. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 26 consecutive patients with massive and fatty degenerative rotator cuff tears were treated surgically. Patients were divided into either the PRCR-SCRB group (n = 14) or SCRTF group (n = 12). Functional outcomes were assessed at final follow-up, and the acromiohumeral distance (AHD) was measured. Results: All functional scores significantly improved in both groups at final follow-up. The PRCR-SCRB group showed better overall outcomes in terms of the visual analog scale for pain; American Shoulder and Elbow Surgeons score; and Quick Disabilities of the Arm, Shoulder and Hand, but these differences were not statistically significant. Better outcomes were found for only the AHD for the PRCR-SCRB group without statistical significance ( P = .4). No statistical difference was found in terms of retear rate. Conclusion: PRCR-SCRB had comparable outcomes and improvement in AHD compared with SCRTF without the need for additional graft harvesting.